PENGARUH MODEL PEMBELAJARAN TAKE AND GIVE UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Astuti Astuti; Lovy Herayanti; Intan Kusuma Wardani (P-2623-0291)
The study aims to find out the influence of 'take and give' learning models on vector subjects. The sample used as a control class was 32 students of class X MIPA 2 and 32 students of class X MIPA 3 as an experiment class. Data collection using pre-test and post-test consisting of 8 essay questions and analyzed using t-test. The results show that the t-test value is lower than the t-table. The study concluded that the 'take and give' learning model had a positive effect on student learning outcomes at SMA Negeri 1 Madapangga in the 2018/2019 school year.